Isolamento e seleção de fungos produtores de lipases: potencial lipolítico de Fusarium oxysporum e da levedura L1 - Izidoro, Simone Cristine (2015)
Due to their biotechnological importance, a great number of studies involving the fungal lipases productionhave been conducted in recent years. The presente study aimed to evaluate the lipases production by fungus isoladed from several habitats. The fungal isolation was conducted employing the succecive dilution technique, allowing the achievementof 54 fungal strains. Of these, 56.37% corresponded to yeast strains, while 43.63% corresponded to filamentous fungi. The lipase production potential were evidenced for all the isolates. However, in the presence of olive oil, the highest levels of lipases were produced by the L1yeast strain (45.92 U/mL) and by the filamentous fungi Fusarium oxysporum (12.16 U/mL), both isolated from contamined oil. In relation to studies regarding the lipase production by the yeast L1, their potential of lipase production in presence was cheese residue was revelead, corresponding to 26.70 U/mL. In the studies envolving the lipases production by the L1 yeast, high levels of lipases were obtained when cheese whey was used as substrate, corresponding a production of 26,70 U/mL. After optimization, using Central Composite Rotatable Design (CCRD) applicable to Response Surface Methodology (RSM), the production levels achieved corresponded to 267,07 U/mL. The best conditions stablished for lipases production by L1 yeast were cheese whey concentration of 1.1%, pH of medium 4.4 and cultivation time of 24 hours. In addition, the F. oxusporum strain was selected in order to be employed in studies of optimization, using CCRD and RSM, in the presence of butia peel The best lipase yields were obtained when the butia peel concentration was 2.9%, the pH of medium was ajusted to 4.2 and the cultivation time was 4.4 days, corresponding to 35.82 U/mL. The biochemical properties of enzymes produced under optimal conditions was also conducted, revealing that the lipases shown optimum activity in neutral pH and 45-50ºC, with high stability in neutral/alcaline pH values and 45ºC. Regarding the effect of several substances on lipase activity, it was observed that ?-mercaptoethanol at 10 mM concentration, as well the ions Ca²+ at 2mM concentration were able to activate these enzymes. Also, an activating effect was observed in the presence of surfactants CTBA and SDS, revealing the potential of these enzymes to be employed in detergente industries. Conversely, the lipases were inhibited by sodium citrate, Mg²+, Pb3+ and EDTA. In relation to the effect of distinct solventes on lipase activity can be noted that only the hexan 20% showed an activating effect. Finally, the lipase sterification activity under different vegetable oils was evaluated. Higher activity levels were observed when the andiroba oil was used, revealing the application potential of these enzymes in biodiesel production from this substrate. The use of cheese whey and butia peel as substrates for lipases production appers to be very promising, since economic and environmental benefits can be obtained from their utilization.